THE THEORETICAL FOUNDATIONS OF A CONCEPT FOR ENHANCING SOFT SKILLS IN TEACHING ENGLISH IN NON-PHILOLOGICAL PROGRAMMES: APPROACHES AND PRINCIPLES (SCIENCE TIME JOURNAL, 2026)
This article examines the theoretical foundations of a concept for enhancing soft skills in teaching English in non-philological programmes. The study is theoretical and conceptual in nature and is based on the analysis of relevant literature and methodological sources. The article identifies the andragogical, competency-based, and activity-based approaches as the main methodological foundation of the concept and formulates key principles such as outcome orientation, integration of language and soft skills, professional relevance, collaboration, reflection, and scaffolding. It is concluded that this framework can support the systematic development of both linguistic competence and transferable skills in higher education.